Role of maintenance treatment on long-term efficacy of bilateral iTBS of the prefrontal cortex in treatment-seeking cocaine addicts: A retrospective analysis - Sanna, Angela; Bini, Valentina; Badas, Paola; Corona, Giorgio; Sanna, Gabriele; Marcasciano, Lara; De Vivo, Maria Chiara; Diana, Marco (Frontiers in Psychiatry, 2022)
CUD, like other addictions, is a chronic disease characterized by a high rate of relapse and drop-out (DO) from medical and behavioural treatment programs, which is positively correlated with relapse. Repetitive transcranial Magnetic Stimulation (rTMS) protocols have shown therapeutic potential in addiction in the short term, but only a few studies have explored their long-term efficacy, so far. This study explores the long-term outcome of bilateral intermittent theta-burst stimulation (iTBS) of the prefrontal cortex (PFC) in cocaine use disorder (CUD) and the possible influence of maintenance treatment in improving abstinence and decreasing DO rates. 89 treatment-seeking CUD patients were exposed to 20 sessions of iTBS. At the end of the treatment 61 (81%) abstinent patients underwent a 12 months follow-up. Among these, 27 patients chose to follow a maintenance treatment (M), whereas 34 patients chose not to adhere to a maintenance treatment (NM). Overall, among patients reaching the 12 months follow-up endpoint, 69,7% were still abstinent and 30,3% relapsed. In NM-patients the DO rate was significantly higher than in M-ones (58.82 % versus 29.63%). The present observations show the long-term therapeutic effect of bilateral PFC iTBS to decrease cocaine consumption. Moreover, they underline the importance to perform a maintenance protocol to consolidate abstinence and decrease DO rates over time.